Distinct anti-NP, anti-RBD and anti-Spike antibody profiles discriminate death from survival in COVID-19 - Servian, Carolina do Prado; Spadafora-Ferreira, Mônica; Anjos, Déborah Carolina Carvalho dos; Guilarde, Adriana Oliveira; Gomes-Junior, Antonio Roberto; Borges, Moara Alves Santa Bárbara; Masson, Letícia Carrijo; Silva, João Marcos Maia; de Lima, Matheus Henrique Assis; Moraes, Brenda Grazielli Nogueira; Souza, Sueli Meira; Xavier, Luiz Eterno; et al. (Frontiers in Immunology, 2023)
Infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induces rapid production of IgM, IgA, and IgG antibodies directed to multiple viral antigens that may have impact diverse clinical outcomes. We evaluated IgM, IgA, and IgG antibodies directed to the nucleocapsid (NP), IgA and IgG to the Spike protein and to the receptor-binding domain (RBD), and the presence of neutralizing antibodies (nAb), in a cohort of unvaccinated SARS-CoV-2 infected individuals, in the first 30 days of post-symptom onset (PSO) (T1). This study included 193 coronavirus disease 2019 (COVID-19) participants classified as mild, moderate, severe, critical, and fatal and 27 uninfected controls. In T1, we identified differential antibody profiles associated with distinct clinical presentation. The mild group presented lower levels and frequency of seropositivity of anti-NP IgG, and IgA (vs moderate and severe), anti-NP IgM (vs critical and fatal), anti-Spike IgA (vs severe and fatal) and anti-RBD IgG (vs severe). The moderate group presented higher levels of anti-RBD IgA, comparing with severe group. The severe group presented higher levels of anti-NP IgA (vs mild and fatal) and anti-RBD IgG (vs mild and moderate). The fatal group presented higher levels of anti-NP IgM and anti-Spike IgA (vs mild), but lower levels of anti-NP IgA (vs severe). The levels of nAb was lower just in mild group (vs severe, critical, and fatal), and revealed no distinguished in the clinical course of the infection. In addition, we studied 82 convalescent individuals, between 31 days to 6 months (T2) or more than 6 months (T3), PSO, those: 12 mild, 26 moderate, and 46 severe + critical. The longitudinal analyzes, for the severe plus critical group showed lower levels of anti-NP IgG, IgA and IgM, anti-Spike IgA in relation to T3. Other side, the follow-up in the fatal group, reveals that the levels of anti-spike IgG increased, while anti-NP IgM levels was decreased along the time. Collectively, our data discriminate death from survival in individuals admitted to the intensive care unit (ICU), suggesting that anti-RBD and anti-Spike IgA may play some deleterious effect, in contrast with the potentially protective effect of anti-NP IgA and IgG.